Make every mother and child count: a retrospective analysis of maternal mortality at medical college tertiary care hospital, Tamilnadu, India - R., Rajarajeswari; M., Poovathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Maternal mortality is a human development indicator. Maternal deaths have serious implication on the family, society and nation. This study is aimed to study the determinants, common causes and recommendations for the prevention of possible causes of maternal mortality. Methods: A retrospective observational study of all maternal deaths for one year period from August 2014 to July 2015 was done in the Department of Obstetrics and Gynaecology, Raja Mirasudhar Hospital, Thanjavur Medical College, Thanjavur, Tamilnadu, India. Results: Over the study period there were 29 maternal deaths out of 14898 deliveries with 14220 live births amounting to a maternal mortality ratio of 204 per 100000 live births. Hypertensive disorders complicating pregnancy were the leading causes of maternal mortality amounting to 40%, while others were haemorrhage - 31%, anaemia with failure 17.2%, heart disease complicating pregnancy 6.4%, sepsis 3.2% and other causes 3.2%. Out of 29 maternal deaths 64.3% were in the age group 21-30 years and 75.7% belonged to lower socio economic status. Conclusions: The Maternal mortality ratio in our study was 204 per 100000live births. Of these the Maternal Mortality Ratio due to intramural deaths was 70 per 100000 live births and Maternal Mortality Ratio due to extra mural deaths (late referral) was 134per100000live births. Hypertensive disorders complicating pregnancy (40%) and its complications mainly HELLP (72.7%) and eclampsia (37.3%) were the most common cause of maternal deaths. Facility based maternal death review and State based maternal death review has contributed a lot in the analysis of the factors causing and compounding maternal mortality and reduction of maternal mortality and its ratio in Tamilnadu.